Análisis de la producción científica visible en internet de los técnicos de salud ambiental del Servicio Andaluz de Salud - GÁMEZ DE LA HOZ, Joaquín; PADILLA FORTES, Ana (Revista General de Información y Documentación, 2010)
Internet it is a powerful interactive communication channel with world scope, through which can be multiplied the visibility of the research of the professionals whose scientific production has a difficult diffusion by the conventionals media. It is presented an analysis of the scientific publications observed in the web in order to understand the different communication processes accomplished by the superior corps of environmental health technical of the Andalusian Health Service. Using the nominal relationship of the professionals, we used Google ‘search engine’ for all scientific publications located in the internet; we were made different bibliometric indicators as of the recovered records and was analyzed the time evolution of the scientific production, documental categories, geografic distribution, language, coauthors and institutional collaboration. It was identified a growing trend in the productivity of the publications in the last decade, mainly through communications to congresses (70.4%) and journals articles (16.9%). The publications mainly are located in spanish journals, that they are indexed on national and international databases. In all the Andalusian provinces was identified some published scientific communication. The indicator of coauthors is very high (95.77%) although the institutional participation is limited mainly to the primary attention districts, occupational centers of each professional (85.21%). The scientific publication patterns visualized in the web represent an important contribution for the knowledge of the characteristics of the environmental health professionals of the Andalusian health service, what provides avaluable information for the support of the information systems in public health.
Keywords: Internet; Web; Scientific publications; Research; Environmental health; Bibliometric indicators